FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS KOMITE AUDIT - Lies Setyo Sri Rahayu; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2014)
This study aims to analyze the factors influencing the audit committee quality. The analysis used independent variable of independent commissioner, competency commissioner, commissioner activity, commissioner size, leverage, the existence of a Big Four auditor, managerial ownership, institutional ownership. And then, company size as control variable.  The dependent variable is audit committee quality. The statistic method to test the hypotheses is multiple linear regression. The sample used is secondary data from the Indonesia Stock Exchange (BEI) is a company's annual report in 2012. Samples were taken at random from the 403 non-financial companies. Eighty non-financial companies designated as the calculation formula Babbie. The results of this research indicate that independent commissioner, competency commissioner, commissioner activity, commissioner size, leverage, the existence of a Big Four auditor, institutional ownership is significantly positive influence the quality of the audit committee. Furthermore, managerial ownership is significantly negative influence the quality of the audit committee. While the leverage does not have a significant influence on the quality of the audit committee.